2016
DOI: 10.4103/0253-7613.178827
|View full text |Cite
|
Sign up to set email alerts
|

Erythema multiforme due to arsenic trioxide in a case of acute promyelocytic leukemia: A diagnostic challenge

Abstract: Erythema multiforme (EM) is an acute, self-limited, Type IV hypersensitivity reactions associated with infections and drugs. In this case of acute promyelocytic leukemia, EM diagnosed during the induction phase was mistakenly attributed to vancomycin used to treat febrile neutropenia during that period. However, the occurrence of the lesions of EM again during the consolidation phase with arsenic trioxide (ATO) lead to a re-evaluation of the patient and both the Naranjo and World Health Organization-Uppsala Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Arsenic trioxide ( 4 ) was approved by the European Commission in 2002 for the treatment of relapsed or persistent acute promyelocytic leukemia (APL) with the trade name of Trisenox ( Cohen et al, 2001 ). Studies showed that Trisenox could promote the apoptosis of leukemia cells by inhibiting DNA methylation ( Badarkhe et al, 2016 ). However, the mechanism of DNA methylation inhibition is unclear.…”
Section: Dna Methyltransferase Inhibitorsmentioning
confidence: 99%
“…Arsenic trioxide ( 4 ) was approved by the European Commission in 2002 for the treatment of relapsed or persistent acute promyelocytic leukemia (APL) with the trade name of Trisenox ( Cohen et al, 2001 ). Studies showed that Trisenox could promote the apoptosis of leukemia cells by inhibiting DNA methylation ( Badarkhe et al, 2016 ). However, the mechanism of DNA methylation inhibition is unclear.…”
Section: Dna Methyltransferase Inhibitorsmentioning
confidence: 99%